Why growth matters: how economic growth in india reduced poverty and the lessons for other developing countries/ by Jagdish Bhagwati and Arvind Panagariya - Bhagwati, Jagdish (New York, 2013)
In its history since Independence, India has seen widely different economic experiments: from Jawharlal Nehru's pragmatism to the rigid state socialism of Indira Gandhi to the brisk liberalization of the 1990s. So which strategy best addresses India's, and by extension the world's, greatest moral challenge: lifting a great number of extremely poor people out of poverty?Bhagwati and Panagariya argue forcefully that only one strategy will help the poor to any significant effect: economic growth, led by markets overseen and encouraged by liberal state policies. Their radical message has huge consequences for economists, development NGOs and anti-poverty campaigners worldwide. There are vital lessons here not only for Southeast Asia, but for Africa, Eastern Europe, and anyone who cares that the effort to eradicate poverty is more than just good intentions. If you want it to work, you need growth. With all that implies.
Keywords: Poverty-India